2019
DOI: 10.1177/2374373519827965
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Infection: A Mixed Methods of Disclosure Pattern and Social Problems in the Nigerian Family

Abstract: Background: Hepatitis B virus (HBV) infection has a high prevalence rate in Nigeria. Disclosure of infection status to close partner and the public attracts support for infected people. This study looks at disclosure and social challenges of infected persons. Methods: Mixed methods of patients’ administered questionnaire and an in-depth interview conducted on HBV-infected respondents in a hospital in Nigeria were used. The study recruited all participants who satisfied the inclusion criteria. Data were entered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…The study had more males than females as well as traders, unemployed, and civil servants. HBV seems to be common among the low socio-economic class in Nigeria and other places (Huang et al, 2016; Adekanle et al, 2019). All participants were equally viremic and could serve as sources of HBV infection, whether male, female, married, or single, but stigma experience was independent of viral level or HBeAg status but based on a positive HBsAg test.…”
Section: Resultsmentioning
confidence: 99%
“…The study had more males than females as well as traders, unemployed, and civil servants. HBV seems to be common among the low socio-economic class in Nigeria and other places (Huang et al, 2016; Adekanle et al, 2019). All participants were equally viremic and could serve as sources of HBV infection, whether male, female, married, or single, but stigma experience was independent of viral level or HBeAg status but based on a positive HBsAg test.…”
Section: Resultsmentioning
confidence: 99%
“…This could also be attributed to the pre-marital laboratory screening testing for would-be couples. A study carried out among Nigerians; higher rate of hepatitis B vaccinations were observed among married couples [43]. This underscores the importance of tailored vaccination strategies targeting different age groups and marital statuses.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in a study by Olusegun Adekanle et al . (2019),[ 22 ] respondents got to know about their disease condition during medical tests for febrile illness, antenatal visit, visa application, general medical tests, pre-employment tests, predonation blood tests, staff screening exercise, and the mandatory national youth service medical tests. This emphasizes the need of a routine medical examination for general population.…”
Section: Discussionmentioning
confidence: 99%